Survey of Migratory Birds (Anatidae: Anas platyrhynchos) for Schistosome Parasites from Mazandaran Province, Northern Iran - A Farahnak; I Mobedi; H Azadeh; MB Molaei Rad; SA Mahdavi (Iranian Journal of Parasitology, 2013)
Background: The aim of the present study was to survey birds' schistosomes in migratory birds (Anatidae: Anas platyrhynchos) which are the source of the disease in Mazandaran Province, Northern Iran.Methods: A number of mallards were bought from the markets of hunted birds. The respiratory tracts (nasal mucosa) and intestinal blood vessels were studied for adult worms. The nasal mucosa was separated and observed by a microscope. In order to separate the visceral schistosomes, after separating intestine, vessel mesenteric was studied under the lamp light and then in saline. The parasite sample was collected for subsequent observation.Results: Fifteen (13.6%) cases out of 110 studied birds had nasal mucosa contaminated with Trichobilharzia sp. egg. Besides that, two birds had adult worms schistosome visceral i.e. Bilharziella sp.Conclusion: The elements that cause cercarial dermatitis in aforementioned region are Trichobilharzia sp. and Bilharziella sp. parasites. Thus, it is necessary for the authorities of health, environmental and agricultural organization of the province to cooperate in order to control this disease.